Public spending and poverty reduction in an oil-based economy: The case of Yemen - Chemingui, Mohamed Abdelbasset (International Food Policy Research Institute, 2007)
This study is part of a collaborative project between the International Food Policy Research Institute and the Arab Planning Institute in Kuwait on public policy and poverty reduction in the Arab region. The purpose of this paper is to assess the impact of an increase in public spending in priority areas on economic growth and poverty reduction in Yemen. To accomplish this objective, the study builds a dynamic Computable General Equilibrium model to provide a baseline scenario of changes in the economy and poverty levels in Yemen during the period 1998-2016. Alternative scenarios are then compared to isolate the specific impact of several policies on poverty. The scenarios assume an increase in public spending devoted to three priority areas (agriculture, education, and health), which affect the economy through an increase in sectoral or economy-wide technical factor productivity. Results of public spending experiments show that targeting increased amounts of public spending towards education and health services will generate more economic growth and poverty reduction than increasing public spending solely on the agricultural sector. However, when an oil sector is a prominent part of the economy, as in Yemen, additional public spending on health and education does not improve productivity in the oil sector. Therefore, spending on agriculture becomes the most important channel for poverty reduction and economic growth. While increasing public spending in priority areas appears to be the best solution available for the government to reduce poverty during the next decade, the road is still long for Yemen to be able to achieve its Millennium Development Goals for poverty reduction. Re-allocating public expenditures from defense to key sectors appears to be an additional option for reducing poverty, given the financial constraints facing Yemen. However, in the current context of terrorism concerns, it will be difficult to convince policy-makers to reduce spending on defense and security. Seeking additional resources from international donors seems to be the only option available to increase benefits from increased public spending in the priority areas identified and assessed in this study.